Training and nutrition for performance: Males, females, and gender differences - López Torres, O.; Fernández-Elías, V. E. (Nutrients, 2024)
As sports nutrition research evolves, a growing body of evidence highlights the importance of sex-based differences in responses to dietary interventions for athletic performance. In particular, the distinct nutritional needs of female athletes and the impact of chronic energy deficits emerge as central themes. Different studies underscore the complexity of nutritional requirements across genders, emphasizing tailored interventions that can support both performance and long-term health outcomes.